Twentieth-century wars in history teaching and public memory of present-day Croatia - Snježana Koren (Firenze University Press, 2016)
Discussions about representations of World War II and the 1990s war in history curricula and textbooks have had a deep impact on the teaching of history in Croatia. Both wars were (and still are) considered as a starting point for the emergence of the (new) state, socialist Yugoslavia in 1945 and present-day Croatia at the beginning of the 1990s. Since 1945, both topics have been used as a means of political legitimization and as an instrument to promote patriotism. The 1941-1945 war was the topic of particular significance in communist Yugoslavia because it was meant to provide the basis of legitimacy for the Yugo-slav Communist regime. During the 1990s, the teaching of this topic underwent dramatic modifications - the manner in which this entire question was treated served as a strong impetus for historical revisionism. In the last couple of years another war has come into the focus of debates about the content of school's history education: the 1991-1995 war, which is called in Croatia the "Homeland War". The conflicting viewpoints of these wars have caused several public debates which have continuously reflected the clash of interpretations and a divided memory that exists in the Croatian society.